2003
DOI: 10.2135/cropsci2003.7970
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity, Specific Combining Ability, and Heterosis in Tropical Maize under Stress and Nonstress Environments

Abstract: Estimation of genetic diversity and distance among tropical maize (Zea mays L.) lines and the correlation between genetic distance (GD) and hybrid performance would determine breeding strategies, classify inbred lines, define heterotic groups, and predict future hybrid performance. The objectives of this study were to estimate (i) heterosis and specific combining ability (SCA) for grain yield under stress and non‐stress environments; (ii) genetic diversity for restriction fragment length polymorphisms (RFLPs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
96
3
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(132 citation statements)
references
References 30 publications
(35 reference statements)
24
96
3
5
Order By: Relevance
“…This has been observed in many previous studies (Godshalk et al 1990;Melchinger et al 1990;Reif et al 2003;Dhliwayo et al 2009;Menkir et al 2010;Badu-Apraku et al 2013) where the predictive ability of markers on performance is generally good only with very closely related lines, where heterosis is likely to be quite low in general. These results are in contrast to Betrán et al (2003b) and Wegary et al (2013) who reported significant correlation between genetic distance and grain yield. The poor correlation between GD and hybrid performance could be attributed to lack of linkage between the SNP markers used to estimate GD and quantitative trait loci for grain yield (Bernardo 1992).…”
Section: Discussioncontrasting
confidence: 99%
“…This has been observed in many previous studies (Godshalk et al 1990;Melchinger et al 1990;Reif et al 2003;Dhliwayo et al 2009;Menkir et al 2010;Badu-Apraku et al 2013) where the predictive ability of markers on performance is generally good only with very closely related lines, where heterosis is likely to be quite low in general. These results are in contrast to Betrán et al (2003b) and Wegary et al (2013) who reported significant correlation between genetic distance and grain yield. The poor correlation between GD and hybrid performance could be attributed to lack of linkage between the SNP markers used to estimate GD and quantitative trait loci for grain yield (Bernardo 1992).…”
Section: Discussioncontrasting
confidence: 99%
“…Betrán et al (2003) reported a highly significant correlation between GD and SCA effects (r = 0.8) in maize under stress and non-stress conditions. Devi and Singh (2011) demonstrated that SCA could emerge as an important factor in the determination of heterosis and per se performance of the hybrids.…”
Section: Introductionmentioning
confidence: 94%
“…Cress (1966) proposed that the extent of GD between parents is necessary for significant heterosis but is not sufficient to guarantee it. Betrán et al (2003) suggested that heterosis can be better predicted only when GD is smaller than a certain threshold. Moreover, studies have suggested that the correlation is dependent on the investigated germplasm and GD calculation methods (Melchinger et al 1990;Tams et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Alguns estudos em diversas espécies têm revelado uma significativa correlação entre distâncias genéticas por marcadores moleculares e expressão da heterose, como em Brassica napus L. (Riaz et al, 2008) e em milho (Betrán et al, 2003). No entanto, em outros estudos têm sido encontradas baixas correlações, como em milho (AjmoneMarsan et al, 1998;Bechimol et al, 2000), em arroz japonica (Kwon et al, 2002), em trigo (Martin et al, 1995;Lorencetti et al, 2006) e em girassol (Cheres et al, 2000).…”
Section: Introductionunclassified